2017
DOI: 10.1002/jtr.2129
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the relationship between push and pull motivational factors in cruise tourism: A canonical correlation analysis

Abstract: Motivation is one of the greatest drivers of human behavior, yet travel motivation in the context of cruise tourism remains an understudied topic. Although a limited number of cruise specific studies focus on push (travel motives) and pull (destination attributes) factors, the push–pull relationship has not been directly measured. Furthermore, pull factors have not been examined in detail in terms of onboard (ship) and onshore (ports of call) attributes. Understanding this relationship can help inform the mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 46 publications
(93 reference statements)
0
29
0
1
Order By: Relevance
“…At present, Chinese tourists have limited understanding of cruise products. Studies have demonstrated that specific information sources can effectively trigger cruise tourists to travel ( Whyte, 2017 ; Sun et al, 2019a , b ). For example, before exposure to cruise information, Chinese tourists were relatively unfamiliar with cruise products, and their intent to travel was often not strong.…”
Section: Methodsmentioning
confidence: 99%
“…At present, Chinese tourists have limited understanding of cruise products. Studies have demonstrated that specific information sources can effectively trigger cruise tourists to travel ( Whyte, 2017 ; Sun et al, 2019a , b ). For example, before exposure to cruise information, Chinese tourists were relatively unfamiliar with cruise products, and their intent to travel was often not strong.…”
Section: Methodsmentioning
confidence: 99%
“…Push and pull theory has been used in tourism research for various types of tourism destinations, such as a nation, a city, or a specific tourist attraction (Kassean & Gassita, 2013; Kim et al, 2003; Noela et al, 2017). The theory has also been applied for different research objects, such as a specific tour (rural tourism, cruise tourism), and travel from a tourism-generating region to a specific destination (Caber & Albayrak, 2016; Suni & Pesonen; 2017; Whyte, 2017). Most researchers have studied both push and pull factors.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Dann (1981) has pointed out that potential tourists in deciding 'where to go' may also consider various pull factors that correspond adequately to their motivational push ' (p. 206). Researchers have empirically examined the relationship between the pull attributes of a destination and the motivational push factors important to travellers (Whyte, 2017). This pull to visit a destination may not trigger an action if the tourist lacks internal drive.…”
Section: Theoretical Background: Theory Of Push and Pull Motivationsmentioning
confidence: 99%
“…Push and pull factors are interrelated and occur at different time points (push precedes pull) (Phau et al, 2013). More importantly, pull factors can not have enough strength unless those are positively triggered by push factors for influencing travel decisions (Whyte, 2017) during the pandemic time. In fact, travellers' internal motivations push them to visit nearby tourist locations during the pandemic time (Chebli & Said, 2020).…”
Section: Conceptual Frameworkmentioning
confidence: 99%